G369(P) The diagnostic utility of bone marrow aspirate in paediatric liver disease. (12th March 2018) - Akhtar, R; Fitzpatrick, E; Hadic, D; Chakravorty, S
Abstract : Aim: To identify the usefulness of bone marrow aspirate (BMA) in the diagnosis of paediatric liver disease in order to prioritise its use in the diagnostic algorithm. Methods: A single-centre 17 year retrospective analysis of BMA procedures in paediatric liver patients was undertaken. Clinical and laboratory data were obtained from the Hospital Electronic Patient Records. Sensitivity and specificity of BMA as a diagnostic tool for Lysosomal storage disorders (LSD) and Haemophagocytic Lymphohistiocytosis (HLH) were computed. Results: A total of 184 paediatric liver patients undergoing 218 BMAs were identified. Of these, BMAs in 137 patients (74.5%) did not have any morphological features suggestive of a specific diagnosis, such as LSD or other haematological conditions (i.e. non-diagnostic). In 84% of children with a final diagnosis of idiopathic liver failure and in 87% with metabolic or developmental liver disease, no specific BMA features were identified. In 116 (63%) patients BMA was specifically undertaken to exclude LSD. A final diagnosis of LSD was made in 14 patients. Thirteen (92.9%) of these patients had morphological features on BMA supporting a diagnosis of LSD. In this case, BMA had an overall sensitivity of 75% (95% CI 42.8%–94.51%) and specificity of 92.55% (95% CI 85.26%–96.95%) in diagnosing LSD. A further nine patients received a diagnosis of HLH. Three (33.3%) of the HLH patients had a diagnostic marrow with a sensitivity of 37.50% (95% CI 8.52%–75.51%) but a specificity of 88.24% (95% CI 63.56%–98.54%). Conclusion: BMA is a safe, quick and effective test to undertake in critically ill children with liver disease, where urgent decisions regarding liver transplantation (LT) need to be taken. It is very useful in the diagnostic algorithm of suspected lysosomal storage disorders, particularly in Niemann-Pick C, where nearly all cases have specific morphological findings and where it requires a significantly longer time to obtain definitive molecular diagnoses. Thus, a morphologically non-diagnostic BMA in children with idiopathic liver failure, metabolic or developmental liver disease allows the clinical team to urgently proceed to LT. Diagnostic yield of BMA in HLH was poor highlighting the diagnostic challenges faced by clinicians in this condition.